The Current Evidence on the Association Between the Urinary Microbiome and Urinary Incontinence in Women - Govender, Yashini; Gabriel, Iwona; Minassian, Vatche; Fichorova, Raina (Frontiers in Cellular and Infection Microbiology, 2019)
Urinary incontinence (UI) is a burdensome condition with high prevalence in middle-aged to older women and an unclear etiology. Advances in our understanding of host-microbe interactions in the urogenital tract have stimulated interest in the urinary microbiome. DNA sequencing and enhanced urine culture suggest that similarly to other mucosal sites, the urinary bladder of healthy individuals harbors resident microbial communities that may play distinct roles in bladder function. This review focused on the urobiome (expanded quantitative urine culture-based or genomic sequencing-based urinary microbiome) associated with different subtypes of UI, including stress, urgency and mixed urinary incontinence, and related syndromes, such as interstitial cystitis and overactive bladder in women, contrasted to urinary tract infections. Furthermore, we examined clinical evidence for the association of the urinary microbiome with responses to pharmacotherapy for amelioration of UI symptoms. Although published studies are still relatively limited in number, study design and sample size, cumulative evidence suggests that certain Lactobacillus species may play a role in maintaining a healthy bladder milieu. Higher bacterial diversity in the absence of Lactobacillus dominance was associated with urgency UI and resistance to anticholinergic treatment for this condition. UI may also facilitate the persistence of uropathogens following antibiotic treatment, which in turn can alter the commensal/potentially beneficial microbial communities. Risk factors of UI, including age, menopausal status, sex steroid hormones and body mass index may also impact the urinary microbiome. However, it is yet unclear whether the effects of these risks factors on UI are mediated by urinary host-microbe interactions and a mechanistic link with the female urogenital microbiome is still to be established. Strategies for future research are suggested.